The Role of Ushul An Nahwu Al Arabi in Improving Arabic Language Competence - Adawiyah, Rabiatun; Al Fatiya, Rufayda (Maliki Interdisciplinary Journal, 2024)
The application of Ushul Nahwu in learning Arabic is the main key in understanding and mastering Arabic sentence structures. Ushul nahwu and nahwu are related in forming good and correct rules. Ushul Nahwu discusses the opinions of the ulama, one of which is the Basrah and Kuffah ulama in formulating the rules of the Arabic language. Apart from that, Nahwu Science plays an important role in developing Arabic language skills, not only focusing on individual abilities in creating sentence structures, but the presence of Nahwu Science can enrich daily communication with four skills which include maharah kalam, maharah kitabah, maharah qiroah and maharah istima' . The difference of opinion of the ulama in naming Ushul An Nahwu is because the culture between the two cities is different so that it can influence the views of ulama from each city towards Arabic and Ushul An Nahwu